Overconfidence and Bubbles in Experimental Asset Markets. Issue 3 (2nd July 2016) - Michailova, Julija; Schmidt, Ulrich
ABSTRACT: This paper investigates the relationship between market overconfidence and occurrence of stock-price bubbles. Sixty participants traded stocks in 10 experimental asset markets. Markets were constructed on the basis of subjects' overconfidence: The most overconfident subjects form high overconfidence markets and the least overconfident subjects low overconfidence markets. Prices in low overconfidence markets tend to track the fundamental asset value more accurately than prices in high overconfidence markets and are significantly lower and less volatile. Additionally, we observe significantly higher bubble measures and trading volume in high overconfidence markets. Two possible explanations for these differences are analyzed: While price expectations are significantly higher in high overconfidence markets, no differences in the average degree of risk aversion were detected.